STUDENTS’ PERCEPTION ON THE IMPORTANCE OF ENGLISH LANGUAGE SKILLS IN TOURISM SECTOR - Nurti Rahayu (LPPM and Travel Operation Department Universitas Asa Indonesia, 2019)
The rapid growth of tourism in Indonesia requires hospitality professionals to be able to communicate effectively in English. A good communication skill is a key element to understand the tourists’ needs which might lead to tourists’ satisfaction. This research aims to elaborate students’ perceptions (N=275) of the importance of communication skills (speaking, reading, listening and writing) in the English language among hospitality students with a descriptive qualitative method. Questionnaires distributed to students consists of two parts; the demographic background together with their previous English learning, and their perceptions of each skill focus. The result findings show students’ view on the importance of each English skills, and it also shows students’ way of learning English. The implications of the research findings can address the weaknesses of students’ English language skills which can be a valuable source for English curriculum developers to improve the English language skills for students